Impact of Divestment Decisions on Shareholders' Wealth - Singh, Jagandeep (Indian Journal of Research in Capital Markets, 2017)
In 2000, Procter & Gamble (P&G) had more than 200 brands in its portfolio. The U.S. based fast moving consumer goods (FMCG) company was growing by leaps and bounds. In the decade that followed, P&G continued its expansion spree through organic and inorganic growth. With revenue of $84 billion in 2012, P&G was the largest FMCG company in the world. The dividend payout to the shareholders was a regular feature for more than five decades. The company had numerous popular brands in its portfolio. These wonderful figures, however, masked a bitter truth. The company's innovation funnel had dried up, and consumers were shifting to low priced alternatives. Unilever, P&G's arch- rival, was increasing its stranglehold in the developing world. P&G decided to become a lean and agile organization through divestments. The company cut costs and improved processes toÂ improve productivity. P&G revisited its diversification strategy and decided to focus on its core and profitable brands. The objective of this study was to examine whether P&G's divestment strategy added value for the company's shareholders. The study used the standard event study methodology to examine the impact of six divestment announcements made by P&G between 2014 and 2016 on shareholders' wealth. The findings of the study suggested that shareholders' of P&G benefitted when the company divested its pets food business. The market reaction was negative when P&G divested its immensely popular Duracell brand. However, no significant abnormal returns were witnessed when P&G sold its Zest and Camay brands to Unilever.